First principle calculations of the stability of nickel phosphides at high pressures - Акилбеков A. Т.; Базарбекулы , Б. А.; Inerbaev , T. M.; Сагатов , Н. Е. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this article, the first principle calculationsfor predicting crystal structures and the relative energy stability of compounds in the Ni–P binary system in the pressure range of 200-400 GPa were performed using computer modeling based on the density functional theory (DFT). It should be noted that the calculations were performed without taking into account the vibrations of atoms (T = 0 K). The search for stable compounds and their structures in the Ni-P system revealed seven new compounds: Ni 14 P, Ni 12 P, Ni 10 P, Ni 8 P, Ni 7 P, Ni 5 P, Ni 3 P и Ni 2 P. All predicted compounds are dynamically stable, which is confirmed by phonon spectra. Spin-polarized calculations were also performed showing the presence of a magnetic moment in structures with a relatively high Nickel content of Ni 14 P, Ni 12 P, and Ni 10 P. Above 350 GPa, the magnetic moment is absent for all predicted compounds, while for pure Ni, the magnetic moment is preserved up to 400 GPa.